Complexity Analysis of Business Processes - Ibl, Martin; Boruchová, Žaneta (IEEE (Institute of Electrical and Electronics Engineers), 2017)
Complexity is a term that is currently used not only in research articles but also in the methodologies and standards used to manage information and projects. The complexity can represent the size of a system, process, program or project, the number of functions and the cost of their acquisition, operation and maintenance. Within the context of this work, the complexity is a variable that represents system properties such as legibility, clarity, comprehensibility, usability, modifiability, easiness of implementation or predictability. With increasing complexity, these characteristics deteriorate and the system becomes more difficult and less effective, for example by increasing its cost, increasing the use of resources, increasing the time and expenses needed for training or maintenance, which may result in a loss of profit for businesses. Different systems or their parts can be compared by complexity measurement. If the system contains elements or bindings that are not necessary, simpler solutions can be created so that its complexity is minimal. This paper presents the process of quantification of complexity in Petri nets and then compares it with other existing approaches. The advantage of the presented complexity measure is the possibility to examine this variable at different levels of system load.
Analýza komplexity v podnikových procesech
Keywords: complexity; process analysis; complexity measure; Petri nets; entropy; komplexita; procesní analýza; měření komplexity; Petriho sítě